Genistein suppresses the inflammation and GSK-3 pathway in an animal model of spontaneous ovarian cancer - Erten, Fusun; Yenice, Engin; Orhan, Cemal; Besir, E. R.; Demirel Oner, Pinar; Defo Deeh, Patrick Brice; Şahin, Kazım (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: Numerous studies show that cancer risk is reduced by consumption of soy-based foods containing genistein, but its effects on the glycogen synthase kinase-3 pathway (GSK-3) in ovarian cancer is unknown. Therefore, we tested the properties of genistein on inflammatory biomarkers and GSK-3 signaling pathways in the ovaries of old laying hens with ovarian cancer. Materials and methods: A total of 300 laying hens were distributed into three groups as follows: group 1, animals fed a standard diet (comprising 22.39 mg of genistein/kg of diet); groups 2 and 3, animals fed a standard diet reconstituted with supplementation of 400 mg or 800 mg of genistein/kg of diet, respectively. Results: Genistein modulated the inflammatory biomarkers by decreasing serum tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), interleukin-8 (IL-8), and vascular endothelial growth factor (VEGF) compared with control (p < 0.001). Moreover, it upregulated insulin receptor substrate-1 (p-IRS-1) and protein kinase B (p-AKT), but downregulated GSK-3 alpha and beta after treatment. It acts in a dose-dependent manner. Conclusion: Genistein exhibited an anticancer effect by reducing proinflammatory biomarkers levels and inhibiting GSK-3 expression in the ovaries of old laying hens. It is a potential candidate in the chemoprevention and/or treatment of ovarian cancer.
Keywords: Genistein; GSK-3; IL-6; TNF-alpha; laying hens; ovarian cancer